Morphogenesis is highly aberrant in the vegetative body of the holoparasite Lophophytum leandrii (Balanophoraceae): All typical vegetative organs are absent and many tissues are highly modified - Gonzalez, Ana Maria (2010)
The vegetative body of Lophophytum leandrii is a ‘‘tuber’’ that completely lacks all vegetative organs typically found in photosynthetic plants. Tubers have a warty surface zone composed of parenchyma cells and brachysclereids; there is no epidermis. The interior of the tuber is a matrix of parenchyma cells and a ramified network of collateral vascular bundles. Ingrowths are abundant in vessels. Tubers grow diffusely by proliferation of parenchyma cells in the matrix and in vascular bundles and by a vascular cambium within each bundle. There are no apical meristems. The innermost portion of the surface zone is also a meristematic region, with warts enlarged by cell proliferation within their centers. The attachment point with Parapiptadenia rigida is a discrete woodrose: a ‘‘coralloid’’ interface caused by localized proliferation of host wood. Infection causes many changes in P. rigida wood development, most of which favor the success of the parasite. The only defensive reaction is that the host stops producing sieve tube members near the infection site. The woodrose and coralloid interface of L. leandrii seem to be intermediate between the simple interface of Helosis, and the elaborate chimeral interfaces of Balanophora and Langsdorffia.